Restorative Justice for Victim’s Rights on Sexual Violence - Sri Wiyanti Eddyono (Journal of Southeast Asian Human Rights, 2021)
Indonesia has experienced very dynamic advocacy for legal reform on the protection of victim of sexual violence. Sexual violence is as emerged issue as the accidents of sexual violence has increased including during COVID 19. There are different ‘initiatives’ to address sexual violence by various actors; first, the law enforcers through their establishment the policy on alternative mechanism outside criminal justice mechanism; seconds, Criminal Code bill lead by Indonesia government under the Ministry on Law and Human Rights; third, the establishment on the anti-sexual violence bill for victim protection initiated by parliaments supported by women’s movements. All the initiatives have claimed has restorative justice approaches which the impact of COVID 19 become one of the arguments. This paper analyzes whether and how ‘restorative justice’ suitable for victim’s rights on sexual violence. This paper argue restorative justice is one of ambitious purpose which integrating in which criminal justice mechanism through legal reform agenda is very problematic particularly where the indicator of restorative justice is unclear. This paper finds although both Criminal Code Bill, Anti-Sexual Violence Bill in some degrees have integrated restorative justice to criminal justice system, the Anti Sexual Violence Bill has more focused to the rights of the victims of sexual violence. However, before these two laws are enacted, there are policies established by law enforcers called restorative justice for sexual violence which is very dilemmatic since the indicator in restoring the rights of women’s victim of sexual violence does not clear. This policy tends to sacrifice victim for offender’s interest.